Widespread transduction of astrocytes and neurons in the mouse central nervous system after systemic delivery of a self-complementary AAV-PHP.B vector. Issue 2 (April 2018) - Rincon, Melvin; de Vin, Filip; Duqué, Sandra; Fripont, Shelly; Castaldo, Stephanie; Bouhuijzen-Wenger, Jessica; Holt, Matthew
Abstract Until recently, adeno-associated virus 9 (AAV9) was considered the AAV serotype most effective in crossing the blood–brain barrier (BBB) and transducing cells of the central nervous system (CNS), following systemic injection. However, a newly engineered capsid, AAV-PHP.B, is reported to cross the BBB at even higher efficiency. We investigated how much we could boost CNS transgene expression by using AAV-PHP.B carrying a self-complementary (sc) genome. To allow comparison, 6 weeks old C57BL/6 mice received intravenous injections of scAAV2/9-GFP or scAAV2/PHP.B-GFP at equivalent doses. Three weeks postinjection, transgene expression was assessed in brain and spinal cord. We consistently observed more widespread CNS transduction and higher levels of transgene expression when using the scAAV2/PHP.B-GFP vector. In particular, we observed an unprecedented level of astrocyte transduction in the cortex, when using a ubiquitous CBA promoter. In comparison, neuronal transduction was much lower than previously reported. However, strong neuronal expression (including spinal motor neurons) was observed when the human synapsin promoter was used. These findings constitute the first reported use of an AAV-PHP.B capsid, encapsulating a scAAV genome, for gene transfer in adult mice. Our results underscore the potential of this AAV construct as a platform for safer and more efficacious gene therapy vectors for the CNS.